Tradução e adaptação transcultural de instrumento de avaliação da consulta farmacêutica - Assumpção, Sandro Martins de (2020)
Introduction: In the last decades, the pharmaceutical profession has witnessed great changes in practice, and this professional has joined the professional health care team, promoting the rationalized use of pharmaceutical drugs. The philosophy of pharmaceutical care is the basis for the services provision and defines that the pharmacists' responsibility is to assist, within their professional limits, all the patient's health needs, including the pharmacotherapeutic ones. Facing a wide variety of services provided by the pharmacist, which makes it difficult to measure the positive impacts resulting from the services provided by this professional, there is a need to evaluate these professionals' abilities in consultations, even if this activity retains individual characteristics, there must be a certain behavior standardization, so that the clinical service is delivered to the patient effectively. Objective: to perform the cross-cultural adaptation and validation for the Portuguese language of the instrument called The Medication-Related Consultation Framework (MRCF). Methodology: Initially, a Scoping Review was carried out with the objective of identifying in the literature the support instruments for pharmaceutical consultations. In this context, two reviewers carried out the selection process, evaluating the titles, abstracts and articles in full. Three categories were used in the title and summary selection: 'yes', 'no' and 'maybe'. About the cross-cultural adaptation of the instrument, this was translated by two bilingual translators, native speakers of Portuguese and proficient in English, did independently the translation to the Portuguese of the original versions of the MRCF instrument. In addition to the above, there was the back translation, synthesis of translations, semantic equivalence of translations, pre-test and evaluation of psychometric properties Results: The instruments included to evaluate the pharmaceutical consultation were: Development and validation of the MedicationRelated Consultation Framework (MRCF); The patient care process (PCP) and Medicine Use Reviews (MUR). The MCRF used The Calgary-Cambridge as a guide, however, this instrument was not included in this review, since it aims to instruct in the process of communication and medical interview. The synthesis of the translations also allowed the performance of grammatical adjustments by the experts, to respect the linguistic rules and avoid bias in the interpretation of items whose translations presented divergent constructions. Conclusion: It is evident that the use of these instruments, as a strategy for standardization of conducts, allows a better evaluation of the pharmaceutical professional, thus contributing to the improvement of the services provided to the patient, as well as having a prominent role in their training.